Dampak Media Sosia terhadap Kesehatan Mental Siswa Remaja - Jalal, Novita Maulidya (Indo-MathEdu Intellectuals Journal, 2024)
The aim of this research is to determine the impact of social media on the mental health of adolescent students. The method in this research is library research which uses 9 scientific articles related to the impact of social media on the mental health of adolescent students. Scientific articles were obtained from national journal literature, nationally accredited journals and international journals. The analysis used was content analysis. The results of this research show that apart from having a positive impact on teenage students, social media also has a negative impact on the mental health of teenage students, including feelings of loneliness and emotional disturbances, stress, addiction and dependence on using social media, cyberbullying, reducing the quality of teenagers' critical thinking. , mood and anxiety disorders, lack of sleep, decreased work productivity, less time with other people, stressed mood, addiction and depression, addiction to pornographic media, and even depression. The conclusion of this research is that although social media can provide benefits in terms of social relationships, its negative impact on the mental health of adolescent students cannot be ignored. Collaborative efforts between parents, educators and teenagers themselves are needed to maximize the benefits of social media while minimizing the risks posed